Analysis of Scalability in Distributed Virtual Environments using the Application-layer Anycasting - Reis, Pedro Henrique [UNESP]; Messias Correia, Ronaldo Celso [UNESP]; Garcia, Rogerio Eduardo [UNESP]; Olivete Junior, Celso [UNESP]; Prates, Jorge Marques [UNESP]; IEEE (Ieee, 2014)
The development of large-scale distributed virtual environments deals with restrictions imposed by the infrastructure of communication systems. The scalability in those systems is an important issue to consider on designing and shows higher complexity, as the resources managed by the system increases. AVDNet - an architecture for scalable distributed virtual environments presented in a previous work - helps to reduce the amount of packets sent over the communication network. Besides, the computational processing on rendering is also reduced by using AVDNet, since the virtual environments is created using regions that separate spatially the environment. However, the AVDNet has restrictions on dealing with bandwidth management and the choice of servers, considering their availability. In this paper we present an analysis of scalability using the application layer anycast. To conduct this analysis we use the AnyAVDNet, a framework that implements the dynamic load distribution among servers of AVDNet regions. In addition, we show the metrics and the results.
Keywords: Distributed virtual environments; scalability; anycast; load distribution